PENGARUH DERAJAT KEASAMAN (pH) TERHADAP KEKERASAN FIBER-REINFORCED COMPOSITE JENIS ULTRA HIGH MOLECULAR WEIGHT POLYETHYLENE (UHMWPE) - , FARIDHA HANUM; , Dr. drg. Siti Sunarintyas, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fiber reinforced composite (FRC) is a material made of plastic matrix that is reinforced by thin fibers. Fiber-reinforced composite is increasingly being used as reinforcement in crown and bridge treatment due to its good mechanical performance. The use of FRC in the oral cavity causes it to interact with saliva, which is easily affected by acidic foods and beverages. The aim of this study was to determine the effect of pH soaking variation on hardness of UHMWPE fibers FRC. used Speciments in this research were FRC with UHMWPE fibers (Construct, Kerr, USA) and flowable composite resin (MasterFlow Biodinamica, Brazil). Block shaped speciments (8x2x2) mm cured with ligh curing unit in 20 s (n=24). Speciments were divided into six groups and soaked in HCl solutions as simulation solutions with pH (7.4